DECOVALEX-2023: An international collaboration for advancing the understanding and modeling of coupled thermo-hydro-mechanical-chemical (THMC) processes in geological systems - Jens T. Birkholzer; Bastian J. Graupner; Jon Harrington; Rick Jayne; Olaf Kolditz; Kristopher L. Kuhlman; Tara LaForce; Rosie C. Leone; Paul E. Mariner; Christopher McDermott; Carlos Plúa; Emily Stein; et al. (Geomechanics for Energy and the Environment, 2025)

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Drivers of population dynamics of at-risk populations change with pathogen arrival - Alexander T. Grimaudo; Joseph R. Hoyt; R. Andrew King; Rickard S. Toomey; Chris Simpson; Cory Holliday; Alexander Silvis; Rick T. Doyle; Joseph A. Kath; Mike P. Armstrong; Virgil Brack; Richard J. Reynolds; et al. (Biological Conservation, 2024)

Investigating leatherback surface behavior using a novel tag design and machine learning - Rick Rogers; Kate H. Choate; Leah M. Crowe; Joshua M. Hatch; Michael C. James; Eric Matzen; Samir H. Patel; Christopher R. Sasso; Liese A. Siemann; Heather L. Haas (Journal of Experimental Marine Biology and Ecology, 2024)

Conservation prioritisation of genomic diversity to inform management of a declining mammal species - Brenton von Takach; Skye F. Cameron; Teigan Cremona; Mark D.B. Eldridge; Diana O. Fisher; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; Ben L. Phillips; Ian J. Radford; Kate Rick; Peter B.S. Spencer; et al. (Biological Conservation, 2024)

More than an anthropogenic phenomenon: Antimicrobial resistance in ungulates from natural and agricultural environments - Lee J. Pinnell; Grace Kuiper; Kate L. Huebner; Enrique Doster; Jennifer K. Parker; Najla Alekozai; Jenny G. Powers; Rick L. Wallen; Keith E. Belk; Paul S. Morley (Science of The Total Environment, 2023)

Streams, sewage, and shallow groundwater: stream-aquifer interactions in the Kathmandu Valley, Nepal - Rajaram Prajapati; Nick N. Overkamp; Niek Moesker; Kate Happee; Rick van Bentem; Anusha Danegulu; Bikesh Manandhar; Nischal Devkota; Amber Bahadur Thapa; Surabhi Upadhyay; Rocky Talchabhadel; Bhesh Raj Thapa; et al. (Sustainable Water Resources Management, 2021)
The Kathmandu Valley in Nepal is facing a water quantity and quality crisis due to rapid urbanization and haphazard water and wastewater planning and management. Annually, groundwater extractions in the Kathmandu Valley exceed capture, resulting in groundwater table declines. Streams are often important sources of recharge to (or destination of discharges from) aquifers. However, stream-aquifer interactions in the Kathmandu Valley are poorly understood. To improve this understanding, we performed topographic surveys of water levels, and measured water quality, in streams and adjacent hand-dug wells (shallow aquifer). In pre-monsoon, 12% (2018) and 44% (2019) of wells had water levels higher than adjacent streams, indicating mostly a loss of stream water to the aquifer. However, in post-monsoon, 69% (2018) and 70% (2019) of wells had water levels higher than adjacent streams, indicating that monsoon rainfall contributes to shallow aquifer recharge which, at least temporarily, causes streams to transition from losing to gaining. Concentrations of all water quality parameters (electrical conductivity, ammonia, alkalinity, and hardness) were higher in the pre-monsoon compared to post-monsoon in both streams and wells. There was no recurring trend in water level difference longitudinally from upstream to downstream. However, water quality in streams and wells depleted from upstream to downstream. While we clearly observed seasonal refilling of the shallow aquifer, the role of the deep aquifer in seasonal storage processes deserve future research attention.

Reef communities show predictable undulations in linear abundance size spectra from copepods to sharks - Freddie J. Heather; Rick D. Stuart‐Smith; Julia L. Blanchard; Kate M. Fraser; Graham J. Edgar (Ecology Letters, 2021)
Among the more widely accepted general hypotheses in ecology is that community relationships between abundance and body size follow a log‐linear size spectrum, from the smallest consumers to the largest predators (i.e. ‘bacteria to whales’). Nevertheless, most studies only investigate small subsets of this spectrum, and note that extreme size classes in survey data deviate from linear expectations. In this study, we fit size spectra to field data from 45 rocky and coral reef sites along a 28° latitudinal gradient, comprising individuals from 0.125 mm to 2 m in body size. We found that 96% of the variation in abundance along this ‘extended’ size gradient was described by a single linear function across all sites. However, consistent ‘wobbles’ were also observed, with subtle peaks and troughs in abundance along the spectrum, which varied with sea temperature, as predicted by theory relating to trophic cascades.

High biomass and productivity of epifaunal invertebrates living amongst dead coral - Kate M. Fraser; Rick D. Stuart-Smith; Scott D. Ling; Graham J. Edgar (Marine Biology, 2021)

Disease alters macroecological patterns of N orth A merican bats - Winifred F. Frick; Sébastien J. Puechmaille; Joseph R. Hoyt; Barry A. Nickel; Kate E. Langwig; Jeffrey T. Foster; Kate E. Barlow; Tomáš Bartonička; Dan Feller; Anne‐Jifke Haarsma; Carl Herzog; Ivan Horáček; et al. (Global Ecology and Biogeography, 2015)
Aim We investigated the effects of disease on the local abundances and distributions of species at continental scales by examining the impacts of white‐nose syndrome, an infectious disease of hibernating bats, which has recently emerged in N orth A merica. Location N orth A merica and E urope. Methods We used four decades of population counts from 1108 populations to compare the local abundances of bats in N orth A merica before and after the emergence of white‐nose syndrome to the situation in E urope, where the disease is endemic. We also examined the probability of local extinction for six species of hibernating bats in eastern N orth A merica and assessed the influence of winter colony size prior to the emergence of white‐nose syndrome on the risk of local extinction. Results White‐nose syndrome has caused a 10‐fold decrease in the abundance of bats at hibernacula in N orth A merica, eliminating large differences in species abundance patterns that existed between E urope and N orth A merica prior to disease emergence. White‐nose syndrome has also caused extensive local extinctions (up to 69% of sites in a single species). For five out of six species, the risk of local extinction was lower in larger winter populations, as expected from theory, but for the most affected species, the northern long‐eared bat ( M yotis septentrionalis ), extinction risk was constant across winter colony sizes, demonstrating that disease can sometimes eliminate numerical rarity as the dominant driver of extinction risk by driving both small and large populations extinct. Main conclusions Species interactions, including disease, play an underappreciated role in macroecological patterns and influence broad patterns of species abundance, occurrence and extinction.